Isis and Sarapis in the Roman world - Takács, Sarolta A. (Religions in the Graeco-Roman World, 1995)
Isis and Sarapis in the Roman World deals with the integration of the cult of Isis among Roman cults, the subsequent transformation of Isis and Sarapis into gods of the Roman state, and the epigraphic employment of the names of these two deities independent from their cultic context. The myth that the guardians of tradition and Roman religion tried to curb the cult of Isis in order to rid Rome and the imperium from this decadent cult will be dispelled. A closer look at inscriptions from the Rhine and Danubian provinces shows that most dedicators were not Isiac cult initiates and that women did not outnumber men as dedicators. Inscriptions that mention the two deities in connection with a wish for the well-being of the emperor and the imperial family are of special significance.